A systematic review, meta-analysis and meta-regression evaluating the adverse reactions to erenumab in the preventive treatment of migraine. Issue 4 (3rd April 2021) - Pellesi, Lanfranco; De Icco, Roberto; Alawie, Hassan Youssef; Andersen, Morten; Liang, David; Amirguliyev, Sarkhan; Al-Karagholi, Mohammad Al-Mahdi; Amin, Faisal Mohammad; Sessa, Maurizio
ABSTRACT: Background : Erenumab has recently been approved as a pharmacological treatment for the prevention of migraine. However, the incidence estimates of adverse drug reactions (ADRs) were not consistent among studies. Consequently, pooled measures of the incidences of ADRs that accounts for inter-study heterogeneity are desirable. In addition, little is known on the factors leading to such heterogeneity. Research design and methods : Clinical trials evaluating the occurrence of ADRs related to erenumab in migraine patients were searched with Ovid MEDLINE until April 2020. Random intercept models were used to estimate the pooled incidence of the ADRs reported at least in 5 different study populations. To examine whether specific factors correlated with the pooled incidence, we performed random-effects meta-regression. Results : Of 138 retrieved references, 8 clinical trials were included in the meta-analysis. We observed a significant heterogeneity of the incidence estimates of back pain, influenza, nasopharyngitis, and upper respiratory tract infection (URTI). Most of the observed heterogeneity is ascribed to treatment duration for back pain ( p = 0.045), influenza ( p < 0.001) and URTI ( p < 0.001), and significantly attributed to Body Mass Index (BMI) for nasopharyngitis ( p < 0.001). Conclusions : Back pain, influenza, nasopharyngitis and URTI showed a significant heterogeneity of incidence estimates.